MAIL SERVER FOR ADDITION TO THE OPERATION OF LOCAL AREA NETWORK EMAIL PT. KUSTODIAN SENTRAL EFEK INDONESIA - Sahroni Sahroni; Don Elsyafitra, SKom (Jurnal Sistem Informasi, 2004)
Management of computer systems and networks in KSEI is sufficient with an interruption occurs infrequently, if an interruption occurs at KSEI system can quickly be overcome so as not to be protracted. IT development in KSEI been conducted in accordance with the scale of needs, the operation of the servers in KSEI has been conducted based on the capabilities and reliability. fifth floor of the living space is very limited network so that the position of the rack is too attached to the wall network. this makes it difficult if will make the changes / additions of material on the shelf network. to reduce so that the room did not look increasingly narrow should the goods not need to do here in this room. Log charging visitors in the computer room must be consistent so that every activity undertaken by outside parties such as vendors listed in the log. This is to avoid unexpected events if there are outsiders who visited the computer room.